Stability of Reconstituted and Diluted Mitomycin C Solutions in Polypropylene Syringes and Glass Vials - Briot Thomas; Truffaut Christine; Le Quay Luc; Lebreton Anne; Lagarce Frederic (De Gruyter, 2016)
Purpose: Mitomycin C (MMC) is widely used in treatment of non-muscle invasive bladder cancer at a 1 mg/mL concentration, by intravesical instillation. MMC is also used as an ophthalmic procedure in glaucoma care mostly with 0.2 mg/mL concentration. To accelerate syringes provision, it could be interesting to demonstrate the stability of the drug, in order to be able to prepare the chemotherapeutic drug several hours before the chemotherapy administration.